2004
DOI: 10.1016/j.febslet.2004.05.065
|View full text |Cite
|
Sign up to set email alerts
|

NaCl‐induced phosphorylation of light harvesting chlorophyll a/b proteins in thylakoid membranes from the halotolerant green alga, Dunaliella salina

Abstract: Light could induce phosphorylation of light harvesting chlorophyll a/b binding proteins (LHCII) in Dunaliella salina and spinach thylakoid membranes. We found that neither phosphorylation was affected by glycerol, whereas treatment with NaCl significantly enhanced light-induced LHCII phosphorylation in D. salina thylakoid membranes and inhibited that in spinach. Furthermore, even in the absence of light, NaCl and several other salts induced LHCII phosphorylation in D. salina thylakoid membranes, but not in spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
23
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 40 publications
9
23
1
2
Order By: Relevance
“…The observed parallel high-salinity-induced increase in phosphorylation of LHCII is in agreement with proposed activation of relevant kinases or alteration in the conformation of LHCII (Liu and Shen 2004).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observed parallel high-salinity-induced increase in phosphorylation of LHCII is in agreement with proposed activation of relevant kinases or alteration in the conformation of LHCII (Liu and Shen 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Liu and Shen (2004) reported that NaCl and several other salts induce LHCII phosphorylation both in vitro or in vivo under dark condition in D. salina but not in spinach. Further evidence indicates that electron inhibitors, 3-(3,4-dichlorophenyl)-1,1-dimethylurea and 2,5-dibromo-3-methyl-6-isopropyl-p-benzoquinone, which are capable of controlling the redox state of PQ, have no effect on the salt-induced phosphorylation level suggesting that the phosphorylation mechanism induced by salt is different from that induced by light and low pH (Liu and Shen 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Many homologous genes encoding LHCPs from various plant species belong to one of the 10 gene family members (Teramoto et al, 2001). Under changing light conditions, the reversible phosphorylation of LHCP a/bbinding proteins (LHCII) represents a system for balancing excitation energy between photosystems I and II (Liu and Shen, 2004). The 11 downregulated DEGs (chlorophyll a/b-binding protein) involved in the photosynthesis pathway were less expressed in Samples 2 and 3 than in the control sample ( Table 4.…”
Section: Downregulated Photosynthesis Contributes To the Damaged Biolmentioning
confidence: 99%
“…Many homologous genes encoding LHCPs from various plant species belong to 1 of the 10 gene family members (Teramoto et al, 2001). Under changing light conditions, the reversible phosphorylation of LHCP of photosystem II represents a system for balancing excitation energy between photosystems I and II (Liu and Shen, 2004). The 11 down-regulated DEGs involved in a photosynthesis pathway were less expressed in NGI and GI samples than in the control sample.…”
Section: Discussionmentioning
confidence: 93%